Shared and fragmented understandings in interorganizational IT project teams: An interpretive case study. Issue 7 (October 2021) - McCarthy, Stephen; O'Raghallaigh, Paidi; Fitzgerald, Ciara; Adam, Frédéric
Highlights: Shared understanding in interorganizational projects cannot be assumed. Interpersonal, technical, and contextual sources of fragmentation in understandings can emerge over time. Project managers must seek to address fragmentation by framing the problem, method, and solution formulation differently. Abstract: Shared understanding is essential in interorganizational projects to integrate the divergent knowledge of individual team members and support collaborative knowledge building. This can nevertheless be a challenging undertaking in interorganizational projects as team members must continuously negotiate differences in their organizational and professional backgrounds during project work. In this paper, we explore how interorganizational IT project teams deal with sources of 'fragmentation' in their understanding, explicating the theoretical and practical implications that these have for project management. Our study is needed to explore the increasingly complex and emergent nature of interorganizational project management today where neither goals nor the means of attainment are known with precision at a project's launch. We analyze interpretive case study findings from an 8-month IT project involving diverse organizations from industry, academia, and healthcare. Based on our findings, we develop a framework which highlights the relationship between three sources of fragmentation of understanding ( interpersonal, technical, and contextual ) across key project activities. We contribute towards project management literature by revealing how these sources of fragmentation might be overcome through framing project activities (the problem, method, and solution formulation ) differently. While fragmentation may characterize any, or all, of these key activities, it is not without remedy.